ISSR markers assisted genetic diversity analysis Dioscorea hispida and selection of best variety for sustainable production - Md Amirul, A.; Nadiawati, Alias; Sarwar, Jahan; Abd Jamil, Z. (2016)
Plant breeding is a way of selection of a particular individual for the production of progeny by separating or combining desired characteristics. The objective of this study is to justify different characteristics of Dioscorea hispida (Ubi gadong) varieties and to select the best variety using molecular techniques for sustainable commercial production at farmer's level. A total o( 160 germplasms of Ubi gadong were collected from different locations at the Terengganu and Kelantan states of Malaysia. Forty eight (48) out of 160 germplasms were selected as 'primary' selection phenotypically based on yield and other qualitative characters. Selected collections were then grown and maintained for ISSR markers assisted genetic diversity analysis. Overall plant growth and yield of tubers were also determined. A total of 12 ISSR markers were tested to justify the characteristics of Ubi gadong varieties among which 3 markers showed polymorphic bands and on an average 57.3% polymorphism were observed representing highest variation among those germplasms. The JSSR marker based on UPGMA cluster analysis grouped an 48 D. hispida into 10 vital groups that proved a vast genetic variation among germplasm collections. Therefore, hybridization should be made between hvo distant populations. The D. hispida is already 1>roved as the highest starch content tuber crops and very rich in vitamins with both micro and macro minerals. Considering all these criteria and results from marker assisted diversity analysis accessions that are far apart based on their genetic coefficient (like DH27 and DH71; DH30 and DH70; DH43 and DH62; DH45 and DH61; DH77 and DH61;DH78 and DH57) could be selected as parents for further breeding programs. This will bring about greater diversity which will lead to high productive index in terms of increase in yield and overall quality and for the ultimate target of sustainable Ubi gadong production.